Micro-RNA 155 controls the pathogenesis of autoimmune arthritis. (22nd February 2011) - Blüml, Stephan; Bonelli, Michael; Niederreiter, Birgit; Puchner, Antonia; Mayr, Georg; Hayer, Silvia; Koenders, Marije I; van den Berg, Wim B; Smolen, Josef; Redlich, Kurt
Abstract : Objective: Micro RNAs (miRNAs) are a new class of regulatory elements. Altered expression of miRNAs has been demonstrated in inflamed joints of patients suffering from rheumatoid arthritis (RA). However, the exact role of miRNAs in the pathogenesis of this disease has not been defined so far. Methods: Collagen induced arthritis (CIA) and K/BxN serum transfer arthritis was induced in wt and miR155 −/− mice. Severity of arthritis was determined clinically and histologically. Anticollagen antibodies and cytokines were measured by ELISA. The cellular composition of the draining lymph node after induction of CIA was measured by flow cytometry. Results: Here the authors show that miR155 −/− mice are completely protected from CIA. miR155 deficiency prevents the generation of pathogenic autoreactive B and T cells since anticollagen antibodies and the generation of antigen specific T cells are strongly reduced in miR155 −/− mice. Moreover, Th17 polarisation of miR155 −/− T cells is impaired as interleukin 17 (IL-17) and IL-22 levels are significantly reduced. Using the K/BxN serum transfer arthritis model, which only depends on innate effector mechanisms, the authors demonstrate that miR155 −/− mice, although developing similar severity of joint inflammation, show significantly reduced local bone destruction due to reduced generation of osteoclasts. Conclusion: Taken together, this study demonstrates that miR155 is essentially involved in adaptive and innate immune reactions leading to autoimmune arthritis, and therefore might provide a novel target to treat RA.